Flax Steeping - Burgess, J. Howard (James Howard), 1817-1890; Hall, S. C., Mrs., 1800-1881 (1840)
Two men steeping flax in a woodland setting.
Title inscribed l.c. on sheet.
Attributed to James Howard Burgess.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43
Keywords: Flax -- Ireland -- 1830-1840; Landscape drawings -- Irish -- 1830-1840.; Pencil drawings -- Irish -- 1830-1840.